HUBUNGAN GURU DAN MURID DALAM PERSPEKTIF AL-QUR'AN DAN HADIS: ANALISIS NILAI-NILAI PENDIDIKAN ISLAM - Panambaian, Tubagus; Bashir, Abdul (AL-ULUM | JURNAL PENDIDIKAN DAN PENGAJARAN, 2025)
This study aims to analyze the teacher-student relationship from the perspective of the Qur'an and Hadith, focusing on the Islamic educational values contained within them. The method used is qualitative research with a library research approach and thematic analysis (tafsir maudhu'i) of primary Islamic sources. The results show that the teacher-student relationship in Islam is not merely an academic interaction but an educative-spiritual relationship based on divine values. Teachers are positioned as murabbi (educators), mu'allim (instructors), and muaddib (character developers) who are responsible for the transfer of knowledge and the formation of character. Meanwhile, students are required to uphold adab al-talib (the ethics of knowledge seekers), which includes attitudes of humility, sincerity, respect, and discipline. Analysis of Qur'anic verses and Hadith reveals five core values in this educative relationship: (1) spiritual value (ukhrawi), (2) moral value (akhlāqī), (3) social value (ijtimā'ī) (4) psychological values (nafsī), and (5) pedagogical values (tarbawī). The implementation of these values in the context of contemporary education faces challenges such as generational differences and the dominance of digital technology, yet they remain relevant as an ethical-pedagogical foundation for character building in the Islamic education system.